Regression analysis of knowledge sharing behavior/ Norfadzilah Abdul Razak, Ramita Abdul Rahim and Maimunah Md. - Abdul Razak, Norfadzilah; Abdul Rahim, Ramita; Md, Maimunah (Universiti Teknologi MARA Cawangan Selangor, 2019)
This paper aims to explore three predictors of Theory Planned Behaviour (attitude, subjective norm and Perceived Behaviors Control) towards the knowledge sharing behavior. Knowledge sharing behavior has become a major issue and is commonly highlighted in the study of knowledge management. Researchers have given serious attention to identify the determinants of knowledge sharing behavior. Employees have to be motivated to share their knowledge and experience in the workplace. In order to influence knowledge sharing behavior among employees, organizations need to understand the tools that drive employees to share their knowledge willingly with others. This paper discusses three predictors of Theory Planned Behavior which have significantly influenced knowledge sharing behavior. A questionnaire survey was administered to the selected group of employees from tourism and hospitality industries in Cyberjaya Malaysia. The 207 employees were participating in this research study. The instrument was adapted from previous study. The result reveals that an absence of attitude is not significantly related to knowledge sharing behavior. However, subjective norms and perceived behavior control relate significantly. This study implies that changes of attitude in individual promote and encourage knowledge sharing behavior positively. The findings of this study proposed to the organization to influence employee to embed the knowledge sharing culture to the employee. The organization needs to change the attitude of employee in term of willingness of them to share knowledge with co-workers. The possibilities of this circumstance happen because of lack awareness of knowledge sharing benefits, lack of rewards and recognition to their contribution and competition among themselves which need to do further study.